2007
DOI: 10.1111/j.1365-313x.2007.03235.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon conversion efficiency and central metabolic fluxes in developing sunflower (Helianthus annuus L.) embryos

Abstract: SummaryThe efficiency with which developing sunflower embryos convert substrates into seed storage reserves was determined by labeling embryos with [U- 14 acids and amino acids was analyzed by NMR and GC-MS. The fluxes through intermediary metabolism were then quantified by computer-aided modeling. The resulting flux map accounted well for the labeling data, was in good agreement with the observed carbon efficiency, and was further validated by testing for agreement with gas exchange measurements. The map sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
179
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(187 citation statements)
references
References 53 publications
7
179
0
1
Order By: Relevance
“…The benefits of this energy source are seen not just in leaves but can also be observed in the metabolism of green seeds (Chen and Shachar-Hill, 2012). Specifically, the additional NADPH allows the refixation of metabolic CO 2 by Rubisco (Schwender et al, 2004), resulting in spectacularly high carbon conversion efficiencies for green oilseeds in the light (Allen et al, 2009b) in comparison with nongreen oilseeds (Alonso et al, 2007(Alonso et al, , 2011 or green oilseeds in the dark (Schwender et al, 2006). In photosynthetic tissues, a major challenge is presented by natural variations in light conditions, which lead to variable rates of photosynthetic NADPH and ATP production.…”
Section: Energy Metabolism In Photosynthetic Tissuesmentioning
confidence: 98%
“…The benefits of this energy source are seen not just in leaves but can also be observed in the metabolism of green seeds (Chen and Shachar-Hill, 2012). Specifically, the additional NADPH allows the refixation of metabolic CO 2 by Rubisco (Schwender et al, 2004), resulting in spectacularly high carbon conversion efficiencies for green oilseeds in the light (Allen et al, 2009b) in comparison with nongreen oilseeds (Alonso et al, 2007(Alonso et al, , 2011 or green oilseeds in the dark (Schwender et al, 2006). In photosynthetic tissues, a major challenge is presented by natural variations in light conditions, which lead to variable rates of photosynthetic NADPH and ATP production.…”
Section: Energy Metabolism In Photosynthetic Tissuesmentioning
confidence: 98%
“…Moreover, the study of the glycolytic enzymatic activities in developing seeds from standard and low oil content sunflower lines, has pointed to phosphoglycerate kinase and enolase as two of the activities probably implicated in the differences in fat content between these lines (Troncoso-Pone et al, 2010a). In addition, labelling and modelling studies have shown that the major source of carbon for the synthesis of fatty acids in sunflower plastids originates from the metabolism of triose phosphates to phosphoenolpyruvate (Alonso et al, 2007). PGK activity is involved in this sequence of reactions, which can take place in the cytosolic and plastidial compartments (Plaxton and Podestá, 2006;Alonso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, labelling and modelling studies have shown that the major source of carbon for the synthesis of fatty acids in sunflower plastids originates from the metabolism of triose phosphates to phosphoenolpyruvate (Alonso et al, 2007). PGK activity is involved in this sequence of reactions, which can take place in the cytosolic and plastidial compartments (Plaxton and Podestá, 2006;Alonso et al, 2007). It is also one of the highest glycolytic activities measured in rapeseed (Brassica napus) embryo cultures (Junker et al, 2007) and has been identified in the group of the most abundant proteins in castor bean (Ricinus communis) developing seeds (Houston et al, 2009), both important crops characterized by high rate of fatty acid synthesis in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 …”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate and acetyl-CoA, the precursors for FA biosynthesis, are synthesized via multiple metabolic routes. For instance, glycolysis and pentose phosphate pathways are the major contributors for pyruvate production in vascular plants, and a minor amount of pyruvate can also be synthesized from malate by NADP-dependent malic enzyme (Kang and Rawsthorne, 1996;Alonso et al, 2007). Pyruvate is then converted to acetyl-CoA by the pyruvate dehydrogenase complex (PDHC) for de novo FA biosynthesis in the plastid (Lutziger and Oliver, 2000;Lin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%